PENGARUH LAPISAN BETON SALURAN IRIGASI TERHADAP KEHILANGAN AIR (STUDI KASUS : DAERAH IRIGASI MENCONGAH) - BAIQ RENI SARI DEWI; MUHAMAD YAMIN (GANEC SWARA, 2022)
Provision of water is very important to support optimal crop yields. However, in some areas there is a problem with not meeting the needs of the rice fields with the available discharge, this is due to several reasons, one of which is the loss of water along the channel during the journey to the rice fields. This study did not review and analyze sedimentation, this study only covered irrigation areas in the primary, secondary and tertiary canals of the Mencongah irrigation area, the type of layer was only limited to soil and concrete.From the results of the study, it was found that the efficiency difference in the channel that had been given a layer of concrete with the channel that had not been coated with concrete, which was obtained for the primary channel of 99 % efficiency, 97% of the secondary channel, while the layer which had not been coated with concrete was the tertiary channel of 87% efficiency.